(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
According to the World Health Organization (WHO), adverse drug reactions (ADRs) are harmful and unintended effects that occur when medications are administered at doses commonly used for disease prevention, diagnosis, treatment, or for altering physiological functions. These reactions constitute a major global public health concern due to their impact on patient safety and healthcare systems worldwide [1]. ADRs are a major cause of morbidity and mortality, particularly in hospitalized patients [2]. Varying patterns of ADRs with non-uniform reporting have been observed in previous studies. The most reported ADRs in Saudi Arabia were in systemic anti-infective agents (22.27%) followed by antineoplastic and immunomodulating agents (21.49%). Specifically, serious ADRs were reported in vancomycin (2.7%), ceftriaxone (1.8 %), fingolimod (1.4 %), and paracetamol (1.4%) [9]. Males have been reported to have more ADRs with the reactions predominantly being cardiovascular (9.9%), followed by dermatological (9.5%) [10]. We aim to investigate ADRs reports at PSMMC we expect greater number of ADRs compared to previous local studies which will give us a clear look at drugs safety and efficacy at our population.